THE THERMODYNAMICS ANALYSE OF LANTERN AT DIENG CULTURE FESTIVAL - Intan Masruroh S; Ayu Mar'ati Barokatun N; Ahmad Khoiri; Nugroho Prasetya Adi (SPEKTRA: Jurnal Kajian Pendidikan Sains, 2023)
This study aims to determine the concept of physics in the form of weather such as rain, wind, and temperature during the flight of the lanterns in the Dieng Culture Festival (DCF) series of events. This research used qualitative research method with literature study method because the data used comes from books, journals, and other documents. The findings in this study are in the form of physics concepts in the flight of lanterns in the series of DCF events. The conclusion is that in the series of DCF events, namely the lantern festival, it can be related to physics, namely the rain and wind conditions in September are not so great that when the lanterns are blown up, they can rise but do not cause the lanterns to disappear into the surrounding villages because of the wind. In addition to the wind, rainfall also affects the Lantern Festival. When heavy rainfall will cause the lanterns to not fly because the heat cannot meet the volume of the lanterns. August to September 2022 is a pretty good month because the wind isn't too fast, the rainfall isn't too dense and the ambient temperature isn't too cold.